Análise da relação entre práticas de autocuidado e Síndrome de Burnout na docência - Silva, Ana Paula dos Santos (2019)
This study aimed to analyze the relation between self-care practices and the dimensions of Burnout Syndrome in teachers, considering the Wallonian theory of the whole person in the unity of the functional fields (affective, cognitive and motor). Self-care, as a practice carried out by the individual to maintain his health and well-being, is an important teachers‟ empowerment tool in the prevention of Burnout Syndrome, because it contributes to the strengthening of those functional fields. Adopting a quantitative approach, data were collected with a stratified random sample of 315 elementary school teachers at public schools of João Pessoa-PB, using three different instruments: 1) a sociodemographic questionnaire, in order to identify teachers‟ profile; 2) Evaluation Scale of the Self-Care Agency - (ASAS-R), aiming to evaluate the self-care capacities of the teachers; 3) Questionnaire for the Evaluation of Burnout Syndrome (CESQT, in Spanish), intending to verify the levels of Burnout symptoms in teachers. Data were submitted to statistical analysis through SPSS Statistics 21.0 and performed Pearson's Correlation Test and Multivariate Analysis, verifying the correlation between self-care and burnout. Results confirmed the proposed thesis, demonstrating the negative relationship between self-care practices and the presence of Burnout Syndrome symptoms, evidencing that the more self-care practices, the less symptoms of this syndrome in the teachers; therefore, these practices tend to positively strengthen our functional unit in the affective, cognitive and motor fields. On the other hand, considering the Wallonian view of functional integration, the Syndrome tends to disintegrate those fields. In relation to the levels of Burnout Syndrome classified as Profile 1 (moderate) and Profile 2 (advanced), we realized a paradox in relation to the Wallonian epistemological model about the constitution of the personal unity by the affective, motor and cognitive fields: Profile 1, seen as a moderate level that does not incapacitate theachers to work, proves to be, by the Wallonian theoretical perspective, the most disintegrated in their fields, since the individual is not aware of his inadequate behaviors (indolent, for example), as well as his state of illness, even if it is beginning. On the other hand, already ill, Profile 2 evidences, in a negative form, the functionality of its motor, affective and cognitive fields (respectively by somatization, demotivation to work and awareness about the personal suffering, the need of self-care or even to change the profession). We conclude by stating the importance of developing a culture of institutional care in schools that encompasses not only individual self-care, but also care in its collective aspects (positive relationships in school, teamwork, pedagogic and ergonomic structure, increase of teaching value, etc.), since, beyond individual aspects, burnout has its roots in institutional factors such as those indicated. In addition, treatment and prevention policies must be carried out and stimulated in order to reduce this syndrome in the teaching field, since both Profile 1 and Profile 2 are highly detrimental to the pedagogical aspects of schooling.